Pentingnya Konseling Pastoral Terhadap Pernikahan Beda Agama di Gereja Masehi Advent Hari Ketujuh - Dolok Bend Franki Pane; Stimson Hutagalung; Exson Eduaman Pane (Jurnal Ilmiah Wahana Pendidikan, 2023)
Interfaith marriage is a scourge that cannot be avoided at this time. Many couples have already been married to people who are not of the same religion as them, which in the end have to face many risks as a result of interfaith marriages. This is a special concern for the Seventh-day Adventist Church because the consequences of interfaith marriages will be able to affect the happiness of the family and the growth of the faith of the couple themselves. The purpose of this study is to provide an overview and understanding to church members on the importance of pastoral counseling for married couples of different religions in the Seventh-day Adventist Church. In this study, the method used was qualitative followed by literature study, by collecting data through books and articles related to pastoral counseling. The results of this study indicate that pastoral counseling is a method that can help church members to be able to cope with stress levels and the risk of unhappiness in domestic life, and can also help young couples who are still dating different religions to understand and understand the risks that will occur when they are married. proceed to marriage. Until finally they can choose and get out of the problems they face.